Derecho administrativo y derechos sociales fundamentales - Jaime Rodríguez-Arana Muñoz (Universidad Hemisferios, 2017)
The aim of this work is to show that the administrative law of a social and democratic state based on the rule of law is the right that the government has to liberty in solidarity. The method used is specific of legal research; in this case through argumentation and by showing the importance that the constitutional principles have on administrative law. The study opens with an introduction where the matter is put forward, followed by an analysis of constitutional law, and a comment on the incidence of the social state clause on Public Administration and administrative law that heralds the main conclusion: that general interest in a social and democratic state based on the rule of law is fully connected to the promotion of the fundamental, individual and social rights of people. In other words, that the dignity of human beings is central and at the root of public law, whereby all its institutions and categories should be defined and built from this perspective.